A systematic comparative analysis of gait characteristics in patients undergoing total knee arthroplasty and unicompartmental knee arthroplasty: a review study - Ming Zhang; Haoyue Wang; Zhiwei Cai; Haochong Zhang; Yifei Zhao; Xiaoran Zu; Cheng Wang; Xiang Li (Journal of Orthopaedic Surgery and Research)
Abstract Background This study systematically reviews recent research comparing clinical outcomes and gait function changes in patients undergoing total knee arthroplasty (TKA) versus unicompartmental knee arthroplasty (UKA). Methods A systematic search of the Web of Science, PubMed, and Embase databases was conducted, covering publications from January 2013 to September 2024, to identify studies evaluating changes in clinical scores and gait parameters in patients undergoing TKA or UKA. Following stringent selection criteria, data were synthesized from studies involving 171 TKA and 148 UKA patients, focusing on reported gait outcomes and aggregating findings for comprehensive analysis. Direct comparisons between TKA and UKA were performed to assess differences in clinical scores and gait parameters, aiming to elucidate the relative efficacy of each surgical approach and provide robust evidence for clinical decision-making. Results Ten studies met the inclusion criteria for post-operative gait outcome comparisons between TKA and UKA, with seven studies also addressing clinical scores. One study reported greater improvement in WOMAC scores for the UKA group at 6 months post-operation (P < 0.05), while another found superior EQ-5D scores for UKA patients at 1 year post-surgery (P < 0.05). Conversely, five studies found no significant differences in clinical scores between groups at 1 year (P > 0.05). All ten studies assessed gait parameter recovery, with three studies showing no significant differences at 1 year (P > 0.05). However, seven studies identified superior gait recovery in the UKA group across various parameters, including walking speed, step and stride length, single support time, heel strike force, knee joint range of motion, knee flexion angles during different gait phases, peak knee adduction moment, peak tibial internal rotation moment, gait symmetry, and stride length symmetry (P < 0.05). Conclusions The analysis indicates that UKA offers certain advantages in post-operative gait improvements compared to TKA, though these do not translate into significant differences in conventional clinical scoring systems. To enhance the reliability and generalizability of these findings, future studies should involve larger-scale, prospective randomized controlled trials.